1997
DOI: 10.1038/sj.pcan.4500212
|View full text |Cite
|
Sign up to set email alerts
|

Day to day changes in free and total PSA: significance of biological variation

Abstract: In this study we evaluated the physiological variation of free and total prostatespeci®c antigen (PSA) levels to determine how the percent freeatotal PSA was affected. Twenty four patients had blood drawn for ten consecutive weekdays. The percent coef®cient of variation (%CV) of biological variation was calculated. The results were log-normally distributed with geometric means of 12.0% CV, 7.3% CV, and 8.8% CV for free, total, and percent freeatotal PSA, respectively. When applied, the percent freeatotal, PSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 7 publications
0
11
0
2
Order By: Relevance
“…Nixon et al calculated the coefficient of variation over 2 weeks and demonstrated that a change between two total PSA measurements of approximately 25% indicated a significant change. [31, 32] Bunting et al reported a critical difference, defined as the minimum percent change between two consecutive measurements that suggests a significant change beyond the normal variation, close to 60% over a time period of 1 year. [33] Bruun et al recently assessed the long-term variability of the different forms of PSA at several different total PSA levels in a randomly selected population of asymptomatic and apparently healthy men whose total PSA levels were <2.0 ng/mL at the end of the 8-year observation period.…”
Section: Total Psa and Its Limitationsmentioning
confidence: 99%
“…Nixon et al calculated the coefficient of variation over 2 weeks and demonstrated that a change between two total PSA measurements of approximately 25% indicated a significant change. [31, 32] Bunting et al reported a critical difference, defined as the minimum percent change between two consecutive measurements that suggests a significant change beyond the normal variation, close to 60% over a time period of 1 year. [33] Bruun et al recently assessed the long-term variability of the different forms of PSA at several different total PSA levels in a randomly selected population of asymptomatic and apparently healthy men whose total PSA levels were <2.0 ng/mL at the end of the 8-year observation period.…”
Section: Total Psa and Its Limitationsmentioning
confidence: 99%
“…Por su parte, The Nacional Cancer Institute define el cribado con PSA como una estrategia que continua en fase de investigación 26 . Las principales razones que alegan sus detractores para desaconsejar el empleo del cribado con PSA son: la elevada tasa de sobrediagnóstico asociado al cribado (definido como aquellos pacientes diagnosticados de CP que no desarrollarían síntomas clínicos a lo largo de Incremento anual > 42% y dPSA > 0,15 ng/mL 48 88, 9 (62,8-99,9) 58,3 (36,5-80,1) 93, 3 (77,4-99,9) 44,4 (18,7-70,2) 41,7 (19,5) Incremento anual > 42% e IPSA < 15% 33 90,0 (66, 9) 65,9 (50,1-81,6) 96,4 (87, 9) 39,1 (17,0-61,3) 34,1 (18,9) Al menos 2 de 3 criterios: 59 55,6 (17,5-93,6) 88, 9 (71,6-99,9) 80,0 (60,0-99, 9) 71,4 (30,9) 11,1 (0,1-28,4)…”
Section: Discussionunclassified
“…Una de las principales aplicaciones de los datos de variación biológica es la estimación del valor de referencia del cambio (VRC), el cual proporciona información sobre cual es el cambio mínimo necesario para que las diferencias entre dos resultados consecutivos de un individuo sean consideradas clínicamente significativas 16,17 . La naturaleza de la variación biológica del PSA total ha sido ampliamente estudiada por numerosos autores [18][19][20][21] , encontrándose en las bases de datos internacionales de variación biológica 22 . Sin embargo, su utilización rutinaria está muy poco extendida, aún cuando el empleo del VRC podría ser una herramienta altamente eficaz para la adecuada interpretación de los cambios en la concentración de PSA a lo largo del tiempo y reducir de este modo el número de pacientes sometidos a biopsias innecesarias.…”
Section: Introductionunclassified
“…Intra-individual PSA variability, even when PSA is measured in the same laboratory, is now established [3]. The studies by Nixon et al [7,8] showed that before a change in PSA level could be ascribed to a real prostatic disease process, there must be a 25% increase. This calculation takes into account biological variation and laboratory issues.…”
Section: Discussionmentioning
confidence: 99%